Abnormal Visual Function: An Under-recognized Risk Factor of Road Traffic Injuries - Hassan Hashemi; Payam Nabovati; Abbasali Yekta; Ali Borojerdi; Hamidreza Fallahkohan; Farhad Rezvan; Mehdi Khabazkhoob (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To determine the relationship between road accidents with visual acuity, refractive errors, visual field, and contrast sensitivity. Methods: This population-based case–control study was conducted on roads leading to Tehran Province, Iran. The case group comprised drivers who had met with accidents and were at fault for the accident. The cases were selected in an ongoing manner (incidence cases). The controls were drivers who were the opposing victims in the same. After an initial interview, optometric and ophthalmic examinations including the measurement of visual acuity, refraction, visual field assessment, contrast sensitivity measurement, and slit lamp biomicroscopy were performed for all study participants. Results: In this study, 281 and 204 individuals were selected for the case and control groups. The mean uncorrected visual acuity was 0.05 ± 0.12 and 0.037 ± 0.10 logMAR in the case and control groups, respectively (P = 0.095). Of the participants in the case and control groups, 32.8% and 23% had a visual field defect in at least one eye, respectively (adjusted odds ratios [aOR] = 1.63, 95% confidence interval [CI]: 1.08–2.48; P = 0.021). Moreover, 16.2% of the cases and 8.3% of the controls had visual field defects in both eyes (aOR = 2.13, 95% CI: 1.17–3.86; P = 0.012). Contrast sensitivity was worse in the case group in all spatial frequencies under non-glare conditions. However, under glare conditions, the contrast sensitivity was significantly worse in the case group only in the spatial frequency of 12 cycles per degree (cpd). Conclusion: Reduced contrast sensitivity, especially under non-glare conditions, and visual field defects are risk factors that influence the prevalence of road accidents. It is strongly advised that special attention be paid to these visual functions in legal assessments to apply the necessary interventions in individuals with these types of disorders.